Sosialisasi Urgensi Ilmu (Kuliah) bagi Generasi Muda di Pondok Salaf Nurul Hidayah Leuwisadeng Bogor - Ali, Agus; Rahmat, Raden Dimas Taufik; Salsabil, Nabila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Knowledge is very important for every individual and can even elevate human dignity. In Islam, seeking knowledge is also an act of worship to Allah with specific goals. The importance of having knowledge is to prove the power of Allah SWT. The goal is to strengthen human belief and faith in Allah SWT. With knowledge, humans can read the Qur'an which contains all the issues on earth and study the universe created by Allah. This type of research is field research conducted by being directly present at the object, especially to gather data and information. The nature of this research is qualitative, producing descriptive data in the form of written or oral words from the people or subjects observed. The PKM on the Socialization of the Urgency of Knowledge (Lectures) for the Younger Generation is aimed at teachers at Pondok Salaf Nurul Hidayah in Bogor Regency and has received enthusiastic responses. The students of Pondok Salaf Nurul Hidayah in Bogor Regency also responded well, even hoping for the socialization/seminar/workshop activities related to the Urgency of Knowledge (Lectures) for the Younger Generation to be good, correct, directed, and sustainable.